KAJIAN PERKEMBANGAN KOGNITIF, AFEKTIF, DAN PSIKOMOTORIK PESERTA DIDIK SEKOLAH MENENGAH PERTAMA DALAM BERWIRAUSAHA - Muhammad Hasan; Putri Hajrah; Thamrin Tahir; Nur Arisah; Inanna Inanna (SOSIOEDUKASI, 2022)
This exploration is directed to determine the mental, emotional, and psychomotor improvement of students in business ventures. This examination was completed using a subjective methodology, which was then depicted by a graphical method. The observers in this study were the educators at SMPN 23 Simbang Maros. The procedure for determining the sources in this review uses a purposive examination strategy, by setting the benchmarks for witnesses, including (1) filling in as instructors and giving data to understudies about the significance of business (2) Assigning at the junior high school level, especially at SMPN 23 Simbang Maros. After being examined subjectively, the results were obtained if the teacher had understood and applied the importance of improving students' mental, feeling, and psychomotor as well as the role of junior high school in the entrepreneurial development of students.